Quantitative computer simulation as a paradigm of scientific investigations - Anon (Universiti Malaysia Perlis, 2010)
Organized by Sustainable Development Unit, Centre for International Affairs and School of Computer & Communication Engineering, 8th June 2010 at Keikhlasan Hall, 10th Floor, KWSP Building, Kangar, Perlis.